Belanja Modal Daerah : Dinamika Ketergantungan Fiskal, PAD, dan SiLPA di Kabupaten Gresik - Rindyi Putri Lestari; Ririt Iriani Sri Setiawati (Academia Open, 2025)
This study aims to analyze the effect of the regional financial dependency ratio, Regional Original Revenue (PAD), and Budget Surplus (SiLPA) on capital expenditure allocation in Gresik Regency. The data used are secondary data from 2009 to 2023 obtained from the Directorate General of Treasury (DJPK) of the Ministry of Finance and the Regional Asset and Finance Management Agency (BPKAD) of Gresik Regency. This study employs a quantitative approach using multiple linear regression analysis. The results indicate that PAD and SiLPA have a significant influence on capital expenditure allocation, while the regional financial dependency ratio does not show a significant influence. These findings suggest that fiscal autonomy and budget efficiency play a key role in driving regional infrastructure development.Highlight : PAD and fiscal dependence significantly influence capital expenditure allocation in Gresik Regency. SiLPA does not significantly affect capital spending, indicating inefficiencies in budget absorption. The study highlights the need for better fiscal planning to optimize infrastructure development. Keywords : Capital Expenditur, Fiscal Dependence, Local Revenue, SiLPA, Local Finance